The Importance of the Fairy Tale in Human Life (Examples of Uzbek and Chinese Fairy Tales.) - Akbarovna, Shakhnoza Nurmatova (European Journal of Life Safety and Stability (2660-9630), 2022)
The article provides a comparative ethnographic analysis to identify national values and cultural meanings through Uzbek and Chinese folk tales. Particular attention is paid to identifying commonalities in folklore, differences in thinking and creativity of the Uzbek and Chinese peoples based on their perceptions of the world and human life.